Islamic Religious Education Study Program at UIN Syarif Hidayatullah and UIN Sunan Gunung Djati - Jejen Musfah; Rusydy Zakaria (TARBIYA: Journal of Education in Muslim Society, 2021)
AbstractThis study aimed to depict the educational process in the Islamic Religious Education Study Program (IRESP) at Islamic States Universities (UIN) of Jakarta and Bandung, such as the recruitment of students, educational process, and their graduates. This study was conducted with a qualitative approach. Data collection techniques used were document study, Focus Group Discussion (FGD), in-depth interviews, and observation. The study concluded: 1) IRESP’s student recruitment system did not produce students with ample basic competences as teacher candidates such as mastering Arabic, teaching materials, and reading and writing the Koran. The recruitment system also ignored the interests and talents of being a teacher. 2) The educational process of IRESP had not been maximized and effective, such as writing papers, Field Experience Program (Program Pengalaman Lapangan/PLP) 1 and 2, and peer teaching. Teaching practice of the students was still minimal. Besides, Teacher and Teaching Staff Training Institutions (Lembaga Pendidikan Tenaga Kependidikan/LPTK) did not have laboratory schools where the students can practice teaching. 3) Graduates of the Islamic Education Departments generally became honorary teachers even though they did not have teaching certificates. Public and private schools or madrasas recruited teachers without the requirement of teaching certificates. This was UIN’s reason for neither immediately designed a pre-service Teachers’ Professional Education (Pendidikan Profesi Guru/ PPG) curriculum nor carried out in-service PPG till now. 4) LPTK had already standard microteaching rooms, the lecturers of LPTK had met the minimum requirement, and learning had used an active approach.AbstrakPenelitian ini bertujuan menganalisis proses pendidikan di Prodi Pendidikan Agama Islam (PAI) di Universitas Negeri Islam Jakarta (UIN) Jakarta dan Bandung, seperti perekrutan mahasiswa, proses pendidikan, dan lulusan. Penelitian ini dilakukan dengan pendekatan kualitatif. Teknik pengumpulan data yang digunakan adalah studi dokumen, Focus Group Discussion (FGD), wawancara mendalam, dan observasi. Studi ini menyimpulkan: 1) sistem rekrutmen mahasiswa PAI tidak menghasilkan mahasiswa dengan kompetensi dasar yang cukup sebagai kandidat guru seperti menguasai bahasa Arab, bahan ajar, dan membaca dan menulis Alquran. Sistem rekrutmen juga mengabaikan minat dan bakat menjadi seorang guru. 2) Proses pendidikan PAI belum maksimal dan efektif, seperti menulis makalah, Program Pengalaman Lapangan (PLP) 1 dan 2, dan peer teaching. Praktik mengajar mahasiswa masih minim. Selain itu, Lembaga Pendidikan Tenaga Kependidikan (LPTK) tidak memiliki sekolah laboratorium tempat mahasiswa dapat berlatih mengajar. 3) Lulusan PAI umumnya menjadi guru meskipun mereka tidak memiliki sertifikat mengajar. Sekolah atau madrasah negeri dan swasta merekrut guru tanpa persyaratan sertifikat mengajar. Ini adalah alasan UIN tidak segera merancang kurikulum Pendidikan Profesi Guru (PPG) pra-jabatan Guru atau melaksanakan PPG dalam jabatan sampai sekarang. 4) LPTK memiliki ruang microteaching yang sesuai standar, dosen LPTK telah memenuhi kualifikasi, dan pembelajaran menggunakan pendekatan aktif.